2012
DOI: 10.1007/s00223-012-9617-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Bone Health in Inflammatory Bowel Disease: A Case–Control Study in 80 Pediatric Patients

Abstract: Previous studies have indicated that children with inflammatory bowel disease (IBD) may not achieve optimal bone mass. We evaluated the skeletal characteristics in children and adolescents with IBD. This cross-sectional cohort study comprised 80 IBD patients (median age 14.9 years, range 5-20) with a median disease duration of 3.4 years; 51 had ulcerative colitis, 26 Crohn disease, and 3 unspecified colitis. Eighty age- and gender-matched healthy subjects served as controls. Areal bone mineral density (aBMD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 38 publications
3
49
1
Order By: Relevance
“…While the risk of long bone fractures may not be increased in children with IBD [55], a cross-sectional study in paediatric IBD showed that vertebral abnormalities from systematic spine X-ray/DXA screening were significantly higher (11%) than healthy controls (3%) [56]. Preliminary results suggest that the risk of fracture of childhood-onset IBD is also increased long-term in adulthood [57].…”
Section: Skeletal Fragility In Paediatric Chronic Diseasementioning
confidence: 99%
“…While the risk of long bone fractures may not be increased in children with IBD [55], a cross-sectional study in paediatric IBD showed that vertebral abnormalities from systematic spine X-ray/DXA screening were significantly higher (11%) than healthy controls (3%) [56]. Preliminary results suggest that the risk of fracture of childhood-onset IBD is also increased long-term in adulthood [57].…”
Section: Skeletal Fragility In Paediatric Chronic Diseasementioning
confidence: 99%
“…It frequently affects children with diffuse connective tissue diseases [21,22], inflammatory bowel diseases [23], chronic renal diseases [24,25], hematological malignancies [26,27,28,29], or solid tumors [30]. Systemic glucocorticoid treatment is associated with an initial increase in bone resorption and a subsequent reduction of bone formation, leading to decreased peak bone mass, microarchitectural deterioration and increased fracture risk [31,32,33,34].…”
Section: Bisphosphonate Use In Pediatric Patientsmentioning
confidence: 99%
“…Low bone mineral density is a common manifestation in Crohn's disease (9,10) and guidelines regarding supplementation are well established (11) . Despite this vitamin D insufficiency remains common.…”
mentioning
confidence: 99%